Effects of Salmonella enterica serovar typhimurium sseK1 on macrophage inflammation-related cytokines and glycolysis. (April 2021) - Lu, Xia; Yu, Chuan; Zhang, Chunjie; Zhang, Hewei; Li, Yinju; Cheng, Xiangchao; Jia, Yanyan
Highlights: SseK1 can down-regulate the production of IL-1β, IL-2, IL-4, IL-6 and IFN-γ. SseK1 can inhibit the pro-inflammatory mediator production of NO. SseK1 can enhance macrophages glycolysis, which may benefit S. Typhimurium survival. Abstract: Salmonella enterica serovar Typhimurium ( S. Typhimurium), an important virulent intracellular pathogen, causes inflammatory gastroenteritis or typhoid. Macrophages play a key role in innate immunity against Salmonella . Salmonella secreted effector K1 (SseK1) encoded by SPI2 has been identified a novel translocated protein. To investigate the role of Salmonella enterica serovar Typhimurium sseK1 about the inflammation and glycolysis in macrophages, the levels of IL-1β, IL-2, IL-4, IL-6, IFN-γ and Nitric Oxide in macrophages infected by S. Typhimurium SL1344 wild-type (WT) group, ΔsseK1 mutant group and sseK1 -complemented group were measured. And the glycolysis level was determined in RAW 264.7 cells infected with these different Salmonella strains. The results showed that groups infected by wild-type strain, sseK1 mutant and sseK1 -complemented strain upregulated the production of IL-1β, IL-2, IL-4, IL-6, IFN-γ and NO at 3 h, 6 h and 12 h, respectively. The production of IL-1β, IL-2, IL-4, IL-6, IFN-γ and NO in wild-type strain group were significantly decreased compared with the Δ sseK1 mutant group, which suggested that sseK1 down-regulated the production of related inflammatory factors. Moreover, hexokinase, lactic acid and pyruvic acid levels significantly decreased by infection with sseK1 mutant compared to the wild-type strain. The ATP level of Δ sseK1 mutant group was remarkably increased than WT group and sseK1 -complemented group. These indicated that the sseK1 enhanced the level of glycolysis of macrophages infected by S. Typhimurium. In summary, the results demonstrated that sseK1 can down-regulate the inflammation-related cytokines and enhance the glycolysis level in macrophages infected by S. Typhimurium, which may be beneficial for S . typhimurium survival in macrophages.